(untitled) (The Review of Diabetic Studies, 2024)
Healthcare practitioners constitute the essential operational foundation of health systems, transforming policy, scientific evidence, and organizational frameworks toward measurable health outcomes. Their responsibilities encompass clinical care, prevention, health education, care coordination, and moral decision-making throughout varied populations and settings. This paper delivers a detailed evaluation of healthcare practitioners’ professional roles, competencies, and their impact on health system performance. It examines the intellectual, relational, and organizational aspects of practice, stressing how practitioners address complexity, uncertainty, and continuity of care. Additionally, the paper discusses workforce issues and presents future tactics to enhance practitioner capacity in reaction to evolving global health needs.